Use of Atomic Absorption Spectrometry in Assessment of Biomonitor Plants for Lead, Cadmium and Copper Pollution - Kaya, Gokce; Yaman, Mehmet (Office Spectroscopy & Spectral Analysis, 2012)
Eleven plant species were collected from the vicinity of lead-battery plant in the city of Gaziantep, Turkey. Lead, cadmium and copper concentrations in the soil and leaves of plants were determined by atomic absorption spectrometry. Lead, Cd and Cu concentrations in the soil samples taken from battery area were found to be in the ranges of 304 similar to 602, 0. 4 similar to 0. 44 and 31 similar to 37 mg . kg(-1), respectively. Significantly increased lead concentration up to 2 750 mg . kg(-1) was found in the leaves of Eleagnus angustifolia L. plant. The lead concentrations in the other plant leaves taken from 50 m around battery factory followed the order Ailanthus altissima > Morus sp. > Juglans regia L. > Ficus carica L. > Cydonia oblonga Miller > Prunus x domestica L. The plants, Populus nigra L., Eleagnus angustifolia L. and Salix sp. were found useful for Cd, and the plant, Eleagnus angustifolia L. for Pb, to be considered as potential biomonitor. Especially, leaves of trees and plants taken from the distance of 50 m from battery plant have relatively higher Pb concentrations. Therefore, people who and animals which live in this area and benefit from these soil and plants have vital risks.
Keywords: Atomic absorption; Lead; Cadmium; Coper; Biomonitor plants; Pollution